(untitled) (Indonesian Journal of Civil Engineering Study, 2025)
This study aims to analyze the satisfaction level of Universitas Semarang students in using online motorcycle taxi applications as the primary mode of transportation to campus. Online motorcycle taxis offer efficient mobility solutions through ease of access, speed, and flexibility, making them a popular choice among students with busy academic schedules. This research employs a quantitative method, with data collected through questionnaires distributed to 100 active undergraduate students at Universitas Semarang. The variables analyzed include service quality, application usability, punctuality, pricing and promotions, and safety. Data analysis was conducted using statistical methods, including validity and reliability tests, linear regression analysis, and descriptive analysis through the SPSS application. The results indicate that most students are reasonably satisfied with the services provided, especially in the aspects of application usability and punctuality. Factors such as service quality and promotions also positively influence satisfaction levels. However, key challenges include fluctuating prices and comfort during trips, which require further improvements. Safety is a primary concern, particularly for students traveling at night. This study also identifies that driver behavior, vehicle conditions, and security features within the application are essential elements influencing user perceptions. The study provides recommendations for online motorcycle taxi service providers to enhance price transparency, develop security features such as emergency buttons and real-time tracking, and offer training programs for drivers to deliver better service. Additionally, it suggests that policymakers consider integrating student needs into digital transportation policies, encompassing accessibility and service sustainability. These findings are expected to be not only relevant for online motorcycle taxi providers but also supportive of student mobility efficiency, contributing to their academic success and offering benefits for the broader development of digital transportation.